On the Uses of the Humanities Vision and Application. A Report by the Hastings Center. (Distributed by ERIC Clearinghouse, 1984)
Designed to provide a general assessment of the rapidly growing applied humanities movement in the United States, this report sets forth issues found to be central to an assessment of current work in the applied humanities, presents a general survey of the nature of applied work in a variety of disciplines, and offers conclusions and observations about how high-quality work in applied humanities can be nurtured and supported in the future. The first of seven sections presents an introduction to issues surrounding the applied humanities movement. The second section examines basic features of current debates related to the humanities by examining three historical developments--Greek thought in the fifth and fourth centuries B.C.; individualism and the reaction against tradition emerging after the Reformation in the West in the 17th and 18th centuries; and professionalization and institutionalization, which began toward the end of the 19th century, reaching maturity during the 20th century. Section 3, "Current Work in Applied Humanities," discusses philosophy, applied and public history, and literature. Section 4 presents models of application while section 5 deals with fields of application--specifically the humanities and the biomedical sciences, humanities and the social sciences, and public policy and the policy sciences. Academic preparation and disciplinary standards are the focus of the next section. The final section summarizes the hopes, problems, and needs of the humanities as a serious discipline of study. (LH)